Pengaruh Promosi, Online Customer Review dan Brand Image terhadap Keputusan Pembelian: Studi pada Waroeng Hokki di Kabupaten Karangasem (Lembaga Pengembangan Kinerja Dosen, 2025)
The background of this research is that there is a gap in previous research regarding the influence of promotion, online customer reviews, and brand image on purchase decisions, as well as management problems faced by Waroeng Hokki in Duda Village, Karangasem Regency, Bali. The main problem is the instability of the number of consumers, which led to a decline in purchasing decisions in 2023- 2024. This situation shows that an effective marketing strategy is essential to increase consumer appeal. This study aims to examine the extent to which promotions, online customer reviews, and brand image affect consumer purchase decisions. This research is based on the Theory of Planned Behavior (TPB), which explains that consumer behavior is influenced by intentions, attitudes, subjective norms, and perceptions of control. This study uses a quantitative method by collecting data through a questionnaire survey, involving 100 respondents, including consumers who have and have never shopped at Waroeng Hokki. The sampling method used is purposive sampling. All data collected were analyzed using SPSS software by multiple linear regression methods, F-test, and t-test. The results of the study show that promotions, online customer reviews, and brand image have a positive and significant influence on purchase decisions. This means that the better the implementation of promotional strategies, customer review management, and brand image formation, the higher the consumer purchase decision. The implications of this study suggest that Waroeng Hokki continue to strengthen promotional activities, actively manage customer reviews, and build a consistent brand image to increase consumer loyalty and competitiveness in the local culinary industry.